The recurring victimization of individuals with mental illness: a comparison of trajectories for two racial groups - Policastro, Christina (Journal of quantitative criminology, 2016)
Objective This study explores whether the trajectories of recurring victimization of Black persons diagnosed with major mental illnesses vary from the trajectories of their White counterparts. Further, the study examines whether the risk factors for recurring victimization among persons with major mental illness vary by race. Methods Using data from the MacArthur Violence Risk Assessment Study (MacRisk), two separate hierarchical binomial regression models were estimated to compare the recurring victimization trajectories of Black and White MacRisk participants. Cross-level interaction terms were also estimated to determine if the coefficients for each of the time-varying covariates included in the analyses were significantly different across race. Results The findings indicate that the trajectories of recurring victimization for Black persons with serious mental illness are significantly different from those of White persons with serious mental illness. Specifically, Black persons’ trajectories remain relatively stable over time, while the risk of recurring victimization declines for Whites as time since release from the hospital increases. Further, the effects of alcohol abuse on revictimization risk vary by race. Conclusion The findings suggest that the life experiences of Black persons with mental illness may be different from their White counterparts, which is likely to contribute to distinct patterns of recurring victimization over time. Future research should continue to explore recurring victimization among diverse samples to identify potential sources of the variation in revictimization trajectories across race.